HUBUNGAN ANTARA AKTIVITAS DENGAN KECAKAPAN BERFIKIR RASIONAL SISWA PADA PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) - Masda Lena; Agus Suyatna; I Dewa Putu Nyeneng (Jurnal Pembelajaran Fisika, 2012)
So far, education in Indonesia is still dominated by teacher oriented classroom as main source of knowledge, so that teachers often ignore student’s initial knowledge. The application of CTL learning is expected to influence students’ rational thinking activities and skills. Based on this background, the researcher conducts a research to find out the correlation between activities and student’s rational thinking skill in CTL learning. The objective of this research is to identify the correlation between activities and student’s rational thinking skill in CTL learning. This research was conducted in Bina Mulya Senior High School in Bandar Lampung by using one experiment classroom (classroom X2) with 39 students as samples. Teacher observed the students’ learning activities when the learning process is taking place. After three times of meeting by using CTL learning, tests for rational thinking skill were conducted by using student’ rational thinking problems that were subsequently processed with correlation tests. The results show that there is a positive and significant correlation between activity and student’s rational thinking skill, and the correlation is strong and it is indicated by value of rcount of 0.756.Keywords: activity, student’s rational thinking skill, CTL learning